Chronic administration of prebiotics and probiotics prevent pathophysiological hallmarks of Alzheimer’s disease in the cortex of APP/PS1 mice - Sarti, Giorgia; Traini, Chiara; Magni, Giada; Attorre, Selene; Tognozzi, Giorgio; Calussi, Edoardo; Giovannini, Maria Grazia; Vannucchi, Maria Giuliana; Lana, Daniele (Frontiers in Pharmacology, 2025)
IntroductionDysbiosis is a characteristic of patients with Alzheimer's disease (AD). The disbalance between Gram-negative and Gram-positive bacteria causes increased production of beta-amyloid (Aβ) in the gut, which can contribute to brain accumulation of Aβ. Recovering microbiota composition with symbiotic administration of prebiotics and probiotics may be a strategy to prevent or reduce AD symptomathology. The aim of this research was to study whether chronic administration of pre- and probiotics modifies the histopathological signs of neurodegeneration in the cortex of APP/PS1 mice, a transgenic mouse model of AD. We focused on neuritic plaques deposition, neuronal degeneration and glia activation.MethodsTransgenic (TG) mice and Wild type (WT) littermates were fed daily with a diet supplemented with prebiotics (a multi-extract of fibers and plant complexes, containing inulin/fruit-oligosaccharides) and probiotics (a 50%–50% mixture of Lactobacillus rhamnosus and Lactobacillus paracasei). The treatment started at 2 months of age and lasted for 6 months. Controls were WT and TG mice fed with a standard diet. All groups were evaluated qualitatively and quantitatively by immunofluorescence, confocal microscopy and digital imaging. Cortical sections were immunostained for neuritic plaques, neurons, astrocytes, microglia, and inflammatory proteins. Qualitative and quantitative analyses were carried out by immunofluorescence, confocal microscopy and digital imaging with ImageJ software.ResultsQuantitative analyses in TG mice demonstrated intense Aβ load and accumulation of neurofilament heavy polypeptide (NHP) in neuritic plaques, neuronal degeneration, shrinkage of the cortex, increase of GFAP expression, and microglia and astrocytes activation. All these effects were mainly evident in cortical Layer 5. The symbiotic treatment with pre- and probiotics decreased Aβ deposition and neuritic plaques in the frontoparietal cortex. In addition, the treatment decreased the degeneration of neurons, the cortical shrinkage, increased GFAP expression, and modified microglia phenomic, decreasing significantly microglia activation. The abovementioned effects of the treatment were mostly evident in cortical Layer 5.DiscussionThese data confirm that prolonged dietary regimen enriched with pre- and probiotics counteracts many of the histopathological hallmarks of AD, and poses the bases for a simple, affordable treatment that may help prevent AD.